2009
DOI: 10.2151/jmsj.87.865
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Polarimetric Radar Variables in Three Types of Rainfalls in a Baiu Front Event over the East China Sea

Abstract: Characteristics of polarimetric radar variables in three rainfall types in a Baiu front event over the East China Sea observed on 1 June 2004 were studied and compared using a C-band polarimetric radar, the CRL Okinawa bistatic polarimetric radar (COBRA). The selected rainfalls are common types in the Baiu season in this area: (1) stratiform type (ST), (2) isolated convective type (ICT) and (3) embedded convective type (ECT). ST was characterized by an obvious bright band in the field of radar reflectivity (Z … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 19 publications
9
33
0
Order By: Relevance
“…Previous studies (e.g., Bringi et al 2006;Shusse et al 2009) have shown that Baiu events show stratiform and convective precipitation. In general, intense (weak) rainfall is generated by convective (stratiform) rain.…”
Section: Classification Of Rain Typesmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies (e.g., Bringi et al 2006;Shusse et al 2009) have shown that Baiu events show stratiform and convective precipitation. In general, intense (weak) rainfall is generated by convective (stratiform) rain.…”
Section: Classification Of Rain Typesmentioning
confidence: 91%
“…The Meiyu-Baiu front brings heavy rainfall in east China, mainly in the Yangtze-Huaihe River basin, and over the southern part of Japan. In recent years, authors have studied the characteristics of DSDs during the Baiu period in Japan (e.g., Harimaya 2003, 2005;Shusse et al 2009;Oue et al 2010); however, not much is known about the DSDs in the Meiyu season in China, mainly because of the lack of DSD measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The volume scan data were interpolated onto a 1 km × 1 km Cartesian grid (i, j, l) at three altitudes, l = 3, 2, and 1 km. The observations were performed in June 2004 during a frontaltype rain event with embedded and isolated convection (Shusse et al 2009). …”
Section: Simulation Of Spaceborne Radar Data Using Ground-based Radarmentioning
confidence: 99%
“…In the humid environment typical of the rainy season in East Asia (called the Baiu season in Japan, Changma in Korea, and Meiyu in China), convective cells with low echo-top heights of approximately 0°C altitude are commonly observed (Zhang et al, 2006;Shusse et al, 2009). Shinoda et al (2007) reported that convective cells with low echotop (30 dBZ) heights less than 1 km above the environmental 0°C altitude accounted for over 70% of convective cells in East Asia during the Baiu period.…”
Section: Introductionmentioning
confidence: 99%